INFLUENCE OF BISTABLE POLARIZED ACTUATOR CORE MAGNETIC PERMEABILITY AND RESISTIVITY ON BREAKAWAY TIME - E.I. Baida (National Technical University "Kharkiv Polytechnic Institute", 2013)
The paper analyzes influence of specific permeability and resistivity of magnetic core material on breakaway time for a vacuum circuit breaker bistable two-position actuator.